2008
DOI: 10.1007/978-3-540-88693-8_58
|View full text |Cite
|
Sign up to set email alerts
|

Improving Shape Retrieval by Learning Graph Transduction

Abstract: Shape retrieval/matching is a very important topic in computer vision. The recent progress in this domain has been mostly driven by designing smart features for providing better similarity measure between pairs of shapes. In this paper, we provide a new perspective to this problem by considering the existing shapes as a group, and study their similarity measures to the query shape in a graph structure. Our method is general and can be built on top of any existing shape matching algorithms. It learns a better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 20 publications
(37 reference statements)
0
109
0
1
Order By: Relevance
“…Note that µ and σ are hyper-parameters. σ is learned by the mean distance to K-nearest neighborhoods [31]. A natural transition matrix on V can be defined by normalizing the weight matrix as:…”
Section: Label Propagationmentioning
confidence: 99%
“…Note that µ and σ are hyper-parameters. σ is learned by the mean distance to K-nearest neighborhoods [31]. A natural transition matrix on V can be defined by normalizing the weight matrix as:…”
Section: Label Propagationmentioning
confidence: 99%
“…Recent work clearly demonstrated that adding context information to direct pairwise shape similarity can substantially improver shape retrieval [40,15,41]. Under context of a given shape we understand here its first K nearest neighbors.…”
Section: Beyond Pairwise Shape Similaritymentioning
confidence: 99%
“…Under context of a given shape we understand here its first K nearest neighbors. However, these methods [40,15,41] mainly focus on improving the transduction algorithms. We demonstrate that a 'better' original distance matrix is also very crucial for the shape retrieval with context information.…”
Section: Beyond Pairwise Shape Similaritymentioning
confidence: 99%
“…Some post-processing methods have been proposed for improving effectiveness of information retrieval tasks [5,18,17,9]. Efforts were put on post-processing the similarity scores by analyzing the relations among all documents in a given collection.…”
Section: Introductionmentioning
confidence: 99%
“…An unsupervised clustering algorithm is used in [5], aiming to capture the manifold structure of the image relations by defining a neighborhood for each data point in terms of a mutual k-nearest neighbor graph. A graph transduction learning approach is introduced in [17]. The algorithm computes the shape similarity of a pair of shapes in the context of other shapes.…”
Section: Introductionmentioning
confidence: 99%